ZAKAT DAN KAJIANNYA DI INDONESIA - Nurfiana Nurfiana; Sakinah Sakinah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2022)
The zakat institution is a body that manages the source of zakat funds received from the Muzakki, both individuals and business entities where the acceptance of zakat is in accordance with applicable Islamic rules or amil receiving zakat, both zakat fitrah and zakat property and zakat in other forms. This study describes zakat and examines zakat institutions in Indonesia. The literature review method is used in this study. The results of this study revealed that zakat institutions play a role in accepting zakat or distributing fund obtained from Muzakki then given to Mustahik. REFERENCES Abbas, A. (2020). Does Zakat Signal the Firm Value? An Additional Inference of Mining and Manufacturing Zakatnomics. International Journal of Zakat, 5(1), 55-66. Fadhillah, N. (2018). Zakat, Pajak Dan Prinsip Keadilan Distributif Islam. QIEMA (Qomaruddin Islamic Economy Magazine), 193. Holil. (2019). Lembaga Zakat Dan Peranannya Dalam Ekuitas. jurnal ekonomi islam, 13. Iqbal, M. (2019). Hukum Zakat Dalam Perspektif Hukum Nasional. Jurnal Asy- Syukriyyah, 47-48. K, A. (2015). Model-Model Pengelolaan Zakat. Jurnal hukum islam, 144. Muslich, D. H. (2018, Agustus 6). Baznas. Retrieved januari 21, 2022, from https://baznaskabserang.or.id/dasar-hukum-zakat-peraturan perundang-undangan/:https://baznaskabserang.or.id/dasar-hukum-zakat-peraturan-perundang-undangan/ Priantina, W. F. (2016). Analisis Penguraian Masalah pada Program Zakat Produktif. Jurnal Al-Muzara'ah, 149-150. Syamsul, Y. B. (2019). Model Pengkuran Kinerja Lembaga Zakat di Indonesia. ZISWAF; Jurnal Zakat dan Wakaf (2019, Vol. 6 No. 1), 45.